DESIGN AND CONSTRUCTION OF A RASPBERRY PI-BASED HUMAN FOLLOWING ROBOT WITH TENSORFLOW LITE-BASED DETECTION - Ariq Farras Zhafran; Dananjaya Ariateja; Herwin Melyanus Hutapea (Universitas Tarumanagara, 2025)
The application of artificial intelligence (AI) in robotics has provided innovative solutions to various operational challenges, particularly those related to the system's ability to automatically detect and interact with humans. One such implementation is the Human Following Robot, an autonomous robot designed to follow human movements using an AI-based image processing system. This research proposes the design and development of a Raspberry Pi 4-based Human Following Robot prototype with a TensorFlow Lite algorithm. The research methodology uses an experimental approach with a focus on evaluating target detection accuracy and robot movement stability under varying lighting and terrain conditions. The experimental approach was used by testing the robot on flat and rocky terrain, as well as in bright and dim lighting conditions. The limitation of this research is that the system only tests the detection of one target person without any obstacles or other people around the robot. The results of the study show that the robot has optimal performance at a detection distance of 200–300 cm with an accuracy of 92%–94% in lighting conditions above 100,000 lux, as well as stable movement on flat terrain. Based on these results, this robot has great potential to support more efficient and safer military logistics operations. Future development will focus on improving accuracy in low-light conditions, improving mechanical design, and integrating multi-object tracking capabilities. Abstrak Penerapan kecerdasan buatan (Artificial Intelligence/AI) dalam bidang robotika telah menghadirkan solusi inovatif terhadap berbagai tantangan operasional, khususnya terkait kemampuan sistem dalam mendeteksi dan berinteraksi dengan manusia secara otomatis. Salah satu implementasinya adalah Human Following Robot, yaitu robot otonom yang dirancang untuk mengikuti pergerakan manusia dengan memanfaatkan sistem pengolahan citra berbasis AI. Penelitian ini mengusulkan perancangan dan pembangunan prototipe Human Following Robot berbasis Raspberry Pi 4 dengan algoritma TensorFlow Lite. Metodologi penelitian menggunakan pendekatan eksperimental dengan fokus penelitian diarahkan pada evaluasi akurasi deteksi target serta kestabilan pergerakan robot pada kondisi pencahayaan dan medan yang bervariasi. Pendekatan eksperimental digunakan dengan menguji robot pada medan datar dan berbatu, serta pada kondisi pencahayaan terang dan redup. Batasan penelitian ini adalah sistem hanya menguji pendeteksian satu orang target tanpa adanya objek penghalang atau orang lain di sekitar robot. Hasil penelitian menunjukkan bahwa robot memiliki kinerja optimal pada jarak deteksi 200–300 cm dengan akurasi 92%–94% pada kondisi pencahayaan di atas 100.000 lux, serta pergerakan stabil di medan datar. Berdasarkan hasil tersebut, Robot ini memiliki potensi besar untuk mendukung operasi logistik militer yang lebih efisien dan aman. Untuk pengembangan selanjutnya diarahkan pada peningkatan akurasi di kondisi minim cahaya, perbaikan desain mekanik, serta integrasi kemampuan pelacakan multi-objek